A new stepwise project management method. (21st June 2006) - Lu, Keh-Ming
A Stepwise Project Management Method (SPMM) is developed to resolve the Project Management (PM) issues. The template of a new stepwise PM method is derived from a Project Management, Inc. (PMI) 19-Step PM method. The 19 Steps were divided into five groups by PMI: scope/requirements, Work Breakdown Structure (WBS), predecessor networks, assigning people to tasks and tracking results. As we view this from a perspective on the principles of management, there exist four basic management functions: planning, organising, leading and controlling. Having rearranged the PMI five groups into four groups of the basic management functions and further skipped the unnecessary steps, a stepwise PM method that is rearranged under the management functions is finally created. The stepwise PM method will be discussed in detail.